Career Competencies for Managing Cross-Cultural Transitions - Arthur, Nancy (Canadian Journal of Counselling and Psychotherapy, 2007)
The changing world of work requires that employees possess a repertoire of cultural competencies for managing their career development. As borders of trade, travel, and immigration shift throughout the world, people need to be prepared for working with others whose cultural background is different to their own. Key demographic and market trends that have impacted the cross-cultural nature of work, a framework for understanding cross-cultural transitions, and core competencies for managing transitions are discussed. Career development practices need to be expanded with both individuals and organizations in a world of work that is increasingly characterized by cross-cultural transitions.